Prevalence Of Intestinal Helminth Infections Among School Aged Children In Elele, South-South Nigeria (Applied Biological Research, 2015)
A study on the prevalence of intestinal helminth infections, using stool  samples of 396 school children comprising of 198 each male and female  randomly selected from 50 households, was conducted in Elele, South South Nigeria, between March and June, 2013. Their basic information  like sex, age and drinking water source were collected using a self administered questionnaire. The prevalence of intestinal helminth  infection varied significantly among males (6.57%) and females (3.4%).  Prevalence also varied significantly among various age groups, with age  group 7-9 having highest infection of Trichuris trichiura (2.25%) while  age group 4-6 had higher prevalence of Strongyloides stercoralis and  Taenia sp. (1.65%). Children within age group 1-3 years had highest  prevalence of Ascaris lumbricoides (2.38%) and finally children within  age group 10-12 were with the highest prevalence rate of hookworm  (1.96%). Similarly the people who drink stream water had higher  prevalence values i.e. 2.27, 3.03, 3.03 and 1.52% for S. stercoralis, A.  lumbricoides, Taenia sp. and hookworms, respectively. T. trichiura was  absent in people who drink stream water while those who drink Sachet  or table water had prevalence rate of 1.52%.
Keywords: Children; helminths; Nigeria; parasites; prevalence